2000
DOI: 10.1001/archopht.118.9.1231
|View full text |Cite
|
Sign up to set email alerts
|

Short-Wavelength Automated Perimetry and Standard Perimetry in the Detection of Progressive Optic Disc Cupping

Abstract: Objective: To compare progression in shortwavelength automated perimetry (SWAP) and white-onwhite (standard) perimetry in eyes with progressive glaucomatous changes of the optic disc detected by serial stereophotographs. Methods: Forty-seven glaucoma patients with at least 2 disc stereophotographs more than 2 years apart, along with standard perimetry and SWAP examinations within 6 months of each disc photo of the same eye, were included in the study. The mean follow-up time was 4.1 years (range, 2.0-8.9 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…11,12,32,33 Previous studies have shown that B/YP is highly sensitive to early glaucoma visual fi eld defects and can predict the development of glaucomatous visual fi eld loss. [8][9][10]12,32 Johnson et al 12 reported that in patients with ocular hypertension, B/YP can reveal early fi eld losses before defi cits can be detected by conventional W/WP. Ferreras et al 34 found that in cases of suspected glaucoma, B/YP detected functional losses before glaucomatous losses were detected by W/WP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,32,33 Previous studies have shown that B/YP is highly sensitive to early glaucoma visual fi eld defects and can predict the development of glaucomatous visual fi eld loss. [8][9][10]12,32 Johnson et al 12 reported that in patients with ocular hypertension, B/YP can reveal early fi eld losses before defi cits can be detected by conventional W/WP. Ferreras et al 34 found that in cases of suspected glaucoma, B/YP detected functional losses before glaucomatous losses were detected by W/WP.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Other studies have shown that unconventional perimetry such as blue-on-yellow perimetry (B/YP) can detect visual fi eld damage earlier than standard white-onwhite perimetry (W/WP). [8][9][10] Both unconventional perimetry and the RNFL can thus be used to detect early glaucomatous damage by different approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 SWAP has some clinical advantages over white-on-white perimetry. SWAP is more sensitive than white-on-white perimetry for the detection of early glaucomatous visual field loss, 21,29,30 is superior to white-on-white perimetry in identifying patients with progressive optic disc cupping 31 and detects visual field loss earlier in patients with ocular hypertension. 30 SWAP is effective in identifying visual field abnormalities in a range of conditions other than glaucoma, such as diabetic retinopathy.…”
Section: Short Wavelength Automated Perimetrymentioning
confidence: 99%
“…Blue-on-yellow perimetry (B/YP) is a type of visual field examination technique, which is a combined method of visual field test and colour vision test. Previous studies have shown that the B/YP is a high-sensitivity method for detecting early visual field defects and predicting the development of visual field loss in glaucoma [23,24,25,26]. …”
Section: Introductionmentioning
confidence: 99%